Global sourcing decisions and firm productivity: evidence from Spain - Wilhelm K. Kohler; Marcel Smolka (Center for Economic Studies and ifo Institute (CESifo), 2009)
We investigate the link between productivity of firms and their sourcing behavior. Following Antràs & Helpman (2004) we distinguish between domestic and foreign sourcing, as well as between outsourcing and vertical integration. A firm's choice is driven by a hold-up problem caused by lack of enforceable contracts. We use Spanish firm-level data to examine the productivity premia associated with the different sourcing strategies. We find strong empirical support for the predictions of the model.
Keywords: F14; F23; L22; L23; 330; productivity; outsourcing; intra-firm trade; foreign direct investment; incomplete contracts; firm-level data